A STUDY ON THE POTENTIAL OF BRAZIL AS AN OFFSHORING SERVICE HUB - Gião, Paulo Roberto; Oliveira Júnior, Moacir de Miranda (Future Studies Research Journal: Trends and Strategies, 2009)
The transfer of part of or an entire value chain to a low-cost site—a practice known as offshoring—has expanded across various countries in the world. Initially, companies began outsourcing their services to developing countries solely to reduce costs, but today, they also continue this practice in order to have access to a qualified workforce. The goal of this study is to identify Brazil’s potential as a service provider for other countries. To this end, a comparison was established between the characteristics of Brazil and India, taking into consideration the drivers that transformed the latter into today’s primary offshoring nerve center. It was verified that despite worldwide acknowledgement of the creative and professional capability of Brazilians, the percentage of fluent English-speaking people is insufficient to allow for the expansion of call centers, back-office services and other kinds of offshoring in Brazil. Key-words: Offshoring, outsourcing, comparative study, Brazil, India.